Image Processing : Dealing with Texture - Petrou, Maria; Kamata, Sei-ichiro (Wiley, 2021)
"Image Processing: Dealing with Textures (2006) has been, for some time, the only book focusing solely on image texture analysis theory, and remains the classic advanced text on the topic. This welcome update brings the original into the 21st century, without abandoning the foundational essentials of this milestone work. Revising author Sei-ichiro Kamata has provided a sympathetic and respectful revision of the late Maria Petrou's original, and delivers an extensive and exhaustive reappraisal worthy of her memory. Chapters receiving complete overhauls include Fractals and Multifractals, Image Statistics, Texture Repair, Local phase Features, Dual tree Complex Wavelet Transform, Ridgelets and Curvelets, and Deep Texture Features. Image Processing: Dealing with Textures 2nd Edition continues the analysis of texture in digital images which are essential to a range of applications in areas as diverse as robotics, defense, medicine and the geo-sciences. It is structured around a series of questions and answers, enabling readers to easily locate information on specific problems. Readers must have some elementary knowledge of Image Processing and Mathematics; there are more advanced topics in this new edition"--